Thirty years of gender differences in self-assessed health - Malnar, Brina (Zdravstveno varstvo, 2013)
Background: This article explores gender trends in self-rated health in Slovenia over the period of thirty years. The main research goals are to examine the associations between gender, social class and health, establish the extent that the patterns of subjective health converge with those in other countries and identify the most vulnerable health groups. Methods: The study is based on six waves of the Slovenian Public Opinion survey carried out between 1981 and 2012 on representative samples of the adult Slovenian population. The main dependent variables are the respondent's self-assessed health and three indicators of psychosomatic health - experiences of insomnia,irregular heartbeat and anxiety. The main independent variables are gender and socio-economic status. The relationship between them was examined using Chi-square tests. Results: The 30 year trend is consistent with prior studies, which found that women report poorer self-assessed health than men. In Slovenia, this gender gap was observed in both social classes, but was more pronounced for women in the lower educated category. The higher prevalence of stress symptoms among women supports the theory of chronic exhaustion resulting from the dual-role strain. Conclusions: In Slovenia the welfare state was able to buffer the adverse effects of increased economic stresses to a significant extent after 1991, resulting in favourable health outcomes for both genders. Dismantling these arrangements may result in short-term financial gains but is likely to trigger long-lasting negative consequences for public health, especially in the case of vulnerable groups such as women.
Keywords: man; moški; razlike; samoocena; Slovenia; Slovenija; woman; zdravje; ženske